Impact of diversification on technical efficiency of organic farming in Switzerland, Austria and Southern Germany - Sebastian Lakner; Stefan Kirchweger; Daniel Hoop; Bernhard Brümmer; Jochen Kantelhardt (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2015)
The paper investigates the impact of subsidies and of para-agriculture on the technical efficiency of organic farms in Switzerland, Austria and Southern Germany. The data-set consists of bookkeeping data with 1,704 observations in the years 2003 to 2005. Technical efficiency is modelled using a stochastic distance-frontier model combined with a Metafrontier-model. The results show almost no efficiency differences among the farms in the three countries. Para-agriculture shows a strong impact on farm's efficiency and output in Austria and Switzerland, whereas in Germany the effect is rather small. The study confirms that agricultural subsidies have a direct impact on farm's efficiency.
Keywords: Q12; Q18; D24; C54; 330; Technical Efficiency; Organic Farming; Grassland Farming; Para-Agriculture